Molecular intravascular imaging approaches for atherosclerosis - Press, Marcella Calfon (2014)
Coronary artery disease (CAD) is an inflammatory process that results in buildup of atherosclerosis, typically lipid-rich plaque in the arterial wall. Progressive narrowing of the vessel wall and subsequent plaque rupture can lead to myocardial infarction and death. Recent advances in intravascular fluorescence imaging techniques have provided exciting coronary artery-targeted platforms to further characterize the molecular changes that occur within the vascular wall as a result of atherosclerosis and following coronary stent-induced vascular injury. This review will summarize exciting recent developments in catheter-based imaging of coronary arterial-sized vessels; focusing on two-dimensional near-infrared fluorescence imaging (NIRF) molecular imaging technology as an approach to specifically identify inflammation and fibrin directly within coronary artery-sized vessels. Intravascular NIRF is anticipated to provide new insights into the in vivo biology underlying high-risk plaques, as well as high-risks stents prone to stent restenosis or stent thrombosis.